Rhizobacterial-plant interactions: conferring to plant growth under drought and salinity stress - Rehman, V.; Kumar, S.M.; Srinivas, V.; Lukeye, J.N.; Gopalakrishnan, S. (Springer, 2025)
The interaction between plants and rhizobacteria plays a critical role in enhancing plant resilience and growth under abiotic stresses such as drought and salinity. Rhizobacteria, particularly plant growth-promoting rhizobacteria (PGPR), possess multiple mechanisms that aid plants in coping with stress conditions. These microorganisms enhance plant growth by producing phytohormones, solubilizing essential nutrients, and synthesizing stress-related compounds, such as osmolytes and exopolysaccharides, which improve root-soil adhesion and soil structure. PGPR also modulate plant stress responses by triggering induced systemic tolerance (IST) and enhancing antioxidant defence mechanisms, thus reducing oxidative damage in plants. Additionally, some rhizobacteria facilitate water uptake and nutrient acquisition by improving root morphology and enhancing soil nutrient bioavailability through nitrogen fixation, phosphate solubilization, and production of siderophores. These interactions collectively enhance plant survival, growth, and productivity in arid and saline environments. Understanding the mechanisms underlying rhizobacterial-plant interactions under stress conditions can pave the way for developing sustainable agricultural practices, especially in drought-prone and saline-affected regions. This chapter highlights the rhizobacterial strategies for alleviating drought and salinity stress and discusses the potential of harnessing these interactions to improve crop resilience under adverse environmental conditions.